Detection of Cryptosporidium sp. in non diarrheal faeces from children, in a day care center in the city of São Paulo, Brazil - Carvalho-Almeida, Therezinha T.; Pinto, Pedro Luis S.; Quadros, Celma Maria S.; Torres, Domingas M.A.G.V.; Kanamura, Hermínia Y.; Casimiro, Angélica Maria (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
The protozoan Cryptosporidium sp. has been frequently detected in faeces from children with persistent diarrhoea. This work achieved to investigate an outbreak of cryptosporidiosis, in a day care center, attending children of high socio-economic level, between 0 and six years old. The outbreak was detected through the network of public health, when stool samples, not diarrhoeic, were examined at the Parasitology Service of the Adolfo Lutz Institute. Among the 64 examined children, 13 (20.3%) showed oocysts of Cryptosporidium sp. in the faeces examined by Kinyoun technique: seven children one year old, three, two years old and three, three years old. Among the 23 examined adults, only a 22 years old woman, possibly having an immunocomprometiment, was positive. Clinical and epidemiological aspects were investigated by questionnaires, highlighting the occurrence of the outbreak in a very dry period.